Forensic mental observations - a comparative analysis of outcome and psychiatric morbidity - Schutte, Tiaan (My University, 2014)
Objective This study aims to compare the outcome and psychiatric morbidity of the forensic mental observation referrals, in the two legally created groups of awaiting trial detainees – the ‘singles’ representing the minor violent and non-violent offenders versus the ‘panels’, representing the seriously violent offenders. Method A cross-sectional, retrospective record review of 200 cases, spanning from January 2010 to August 2010, of all individuals admitted to the Forensic unit of Sterkfontein Hospital, for 30 days psychiatric observation. The Pearson’s Chi squared test for categorical data was used to determine statistical significance. Results Of 110 ‘singles’ 49 (44.55%) were found fit for trial and 40 (40.4%) criminally responsible, whereas of the 90 ‘panel’ cases 60 (66.67%) were fit for trial and 57 (64.77%) were criminally responsible. (p = 0.002 and 0.001 respectively) Conclusion Those charged with seriously violent offences appear to be more likely to be found both fit and responsible, compared to those charged with less serious offences.
Keywords: Forensic Psychiatry